Unusual Clinical and Biochemical Presentations of Severe Covid-19 Pneumonia Managed in General Ward (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Covid-19 is a multi-system infection which predominately infects the lungs. This new disease can present as an asymptomatic infection to life threatening infections leading to death, making it a challenge for healthcare workers across the globe in this pandemic. Covid-19 pneumonia often shows a set pattern of symptom progression along its disease course, although the timing of each symptom may vary in different individuals. In this case report, we will discuss the unusual presentation of a middle-aged man who suffered a prolonged course of disease and who was managed on suspicion of a secondary bacterial infection along with cytokine storm. The logical, thoughtful management options that we chose at various stages of his disease in general ward without use of immune modulatory drug like tocilizumab,which eventually led to his cure are also discussed here.Persistence of positive RT-PCR in the 4th  week is also seen in this case.Emphasis is given on how these tricky cases can be dealt in the general ward without shifting them in the HDU, where HDU or ICU facilities are not available or affordable.J Bangladesh Coll Phys Surg 2020; 38(4): 223-228